PERSATUAN ISLAM TIONGHOA INDONESIA (PITI) BANYUMAS (STUDI TENTANG EKSISTENSI DAN AKULTURASI BUDAYA) - Sriyanto, Agus (Jurnal Penelitian Agama, 2013)
The religious conversion among Chinese people, i.e. they converted to Muslims, has brought sociological problems to them. After their conversion to islam, they are alienated and not accepted in their previous community. For that reason, many Chinese muallaf try to find new friends of the similar experience as muallaf. PITI (the Association of Tionghoa Muslims) was established to give advocation and protection to such people. The role of Banyumas Regency PITI are to give a religious understanding and give capital for them in running their business. This is intended to make them able to get into a new society after they are ignored by their previous community. The contact between Chinese and Islamic traditions in such a case has caused an acculturation in the society.